2021
DOI: 10.1021/acssuschemeng.1c01095
|View full text |Cite
|
Sign up to set email alerts
|

Premagnetized Carbon-Catalyst Interface Delivering 650% Enhancement in Electrocatalytic Kinetics of Hydrogen Evolution Reaction

Abstract: Manipulating heterogeneous electrified interfaces with an external magnetic field (H ext) explicitly mandates the constant presence of H ext for achieving magnetoelectrocatalytic kinetic enhancements. Here, we demonstrate the highest kinetic enhancement of 650% in electrocatalytic hydrogen evolution reaction (HER), without the mandatory presence of H ext. A synergistic interface created in nanostructured hard carbon florets (NCF) decorated with ferro–paramagnetic nanoparticles (Co3O4, Co, and Ni–Co) is demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Saha et al reported that the ferro-paramagnetic coupling at the metal (Co 3 O 4 , Co and Ni-Co)/carbon nanotube interface decreased the magnetoresistance and hence charge transfer resistance. 275 Furthermore, the dynamic swelling (volumetric expansion) of the interfacial catalyst was observed upon magnetization, leading to increased ECSA.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…Saha et al reported that the ferro-paramagnetic coupling at the metal (Co 3 O 4 , Co and Ni-Co)/carbon nanotube interface decreased the magnetoresistance and hence charge transfer resistance. 275 Furthermore, the dynamic swelling (volumetric expansion) of the interfacial catalyst was observed upon magnetization, leading to increased ECSA.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…This implies that the four CFO nanocrystals might undergo a deformation of volume expansion upon magnetization, leading to an increase in ECSA and expansion of the active sites. 49 Due to the coupling effect of the magnetic moments of unpaired electrons in the atom and the spin−orbit coupling effect, the lattice in the magnetic domain is distorted under the magnetic field, which is manifested as a change in the volume and shape of the magnetic domain and ferromagnetic particles. 50,51 The results presented above suggest that both the spin polarization effect and ECSA effect are pathways for the magnetic field to affect the OER process of CFO nanocrystals.…”
mentioning
confidence: 89%
“…As opposed to most previous studies, the electrochemically active surface area (ECSA) of the CFO catalyst was changed during the reaction. , To this end, cyclic voltammetry (CV) tests in the non-Faraday region (−0.02 to 0.08 V) were carried out at different scan rates (Figure S9), where the electrochemical double-layer capacitance ( C dl ) is increased under a magnetic field of 14000 G. Consequently, the calculated ECSA values are increased by 1.995 (CFO 3900 Oe), 1.573 (CFO 4500 Oe), 0.885 (CFO 6300 Oe), and 0.355 cm 2 (CFO 7500 Oe), respectively (Figure c). This implies that the four CFO nanocrystals might undergo a deformation of volume expansion upon magnetization, leading to an increase in ECSA and expansion of the active sites . Due to the coupling effect of the magnetic moments of unpaired electrons in the atom and the spin–orbit coupling effect, the lattice in the magnetic domain is distorted under the magnetic field, which is manifested as a change in the volume and shape of the magnetic domain and ferromagnetic particles. , The results presented above suggest that both the spin polarization effect and ECSA effect are pathways for the magnetic field to affect the OER process of CFO nanocrystals.…”
mentioning
confidence: 93%
“…Third method is having key advantages like, 19% reduction in energy, 3 times increase in the rate of Hydrogen production and 650% increase in current density. It can be called as magneto-electrolytic hydrogen generator (MEHG) (Jayeeta Saha, Ranadeb Ball, & Chandramouli Subramaniam, 2021). As our application is completely based on the efficiency of electrolysis, it seems logical to consider the MEHG.…”
Section: Advanced 5 Kw Electrolyzer Having External Magnetic Effectsmentioning
confidence: 99%